Análise técnico-tática do ataque de uma equipe de voleibol feminina de alto nível - Fernandes, Gabriel Jungles (2013)
Attack, in volleyball, is a technical skill that takes place after the set. Its composition starts after the ball is received as an attack or serve, and the setters place it in the air so a player may attack the ball. This paper aims to evaluate the effectiveness of this skill, when made from the position 1 of the court. The evaluation will take in consideration two different tactical formations: the side-out, which is the first offensive formation after the adversary’s serve; and the counterattack, the offensive positioning after the opponent’s attack. Moreover, this work intends to quantify the attack incidence in different areas of the volleyball court. The analyzed data consist in five official matches of the Superliga, season 2009/2010, extracted from public domain websites, in a total of 15 sets and 203 attack actions made by the opposite hitter. The analyses applied the SOS-vgs (Observation and Evaluation System for Distribution in real play situation), and the Chi-squared test (x²) as well, in order to verify the frequency of variables p < 0.05 in the SOS-vgs tool. The variables related to the Conditions for Distribution resulted in expressive values. The frequencies showed a better effectiveness of the attacker in transition or counterattack positions, though, also showed a regularity in all the situations pointed by the analysis tool. Regarding the attack incidence, the deeper areas of the court (areas 1 and 6), presented a higher frequency in the actions accounts.